2012
DOI: 10.1016/j.mayocp.2012.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The Hygienic Efficacy of Different Hand-Drying Methods: A Review of the Evidence

Abstract: The transmission of bacteria is more likely to occur from wet skin than from dry skin; therefore, the proper drying of hands after washing should be an integral part of the hand hygiene process in health care. This article systematically reviews the research on the hygienic efficacy of different hand-drying methods. A literature search was conducted in April 2011 using the electronic databases PubMed, Scopus, and Web of Science. Search terms used were hand dryer and hand drying. The search was limited to artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 52 publications
4
112
0
5
Order By: Relevance
“…Nur "jet air" Händetrockner mit Infrarot erwiesen sich bei 10 s Anwendung dem Papierhandtuch in der Trocknungswirkung gleichwertig [224]. Da nach Händewaschung durch sorgfälti-ge Händetrocknung die Translokation von Bakterien von den Händen auf Kontaktflächen signifikant herabgesetzt wird [221,225], ist auch unter diesem Gesichtspunkt die Händetrocknung wichtig [226,227]. Allerdings war nach vorher durchgeführter Händedesinfektion keine erhöhte Translokation durch Heiß-lufttrockner nachweisbar [228,229].…”
Section: Ausstattung Medizinischer Handwaschplätzeunclassified
See 1 more Smart Citation
“…Nur "jet air" Händetrockner mit Infrarot erwiesen sich bei 10 s Anwendung dem Papierhandtuch in der Trocknungswirkung gleichwertig [224]. Da nach Händewaschung durch sorgfälti-ge Händetrocknung die Translokation von Bakterien von den Händen auf Kontaktflächen signifikant herabgesetzt wird [221,225], ist auch unter diesem Gesichtspunkt die Händetrocknung wichtig [226,227]. Allerdings war nach vorher durchgeführter Händedesinfektion keine erhöhte Translokation durch Heiß-lufttrockner nachweisbar [228,229].…”
Section: Ausstattung Medizinischer Handwaschplätzeunclassified
“…Nach Händewaschung wird durch Papier-oder Textilhandtuch signifikant mehr Restflora als durch Heißlufttrockner entfernt [230][231][232]. Schließlich ist bei der Auswahl des Trocknungssystems zu berück-sichtigen, dass Nutzer bezüglich Komfort und Nutzerfreundlichkeit Einmalhandtü-cher gegenüber Heißlufttrocknern bevorzugen [226] und die Lärmbelastung bei "jet air" Trocknern in 0,5 m Entfernung 94 dB erreicht [224]. Für einen "air blade" Trockner wurde ermittelt, dass die Anzahl freigesetzter Tröpfchen beim Trocknungs-vorgang höher war und weiter reichte als bei Benutzung eines Papierhandtuchs.…”
Section: Ausstattung Medizinischer Handwaschplätzeunclassified
“…For this it was based on hand drying equipment present in several bathrooms. The reference drying time announced by most manufacturers is 10 s [24]. Comparing the hand area, about 0.0896 m2 [25], and the body area, about 1.8 m2 [26], and considering that the body dryer equipment has twice the flow rate of the hand dryer, the ventilation drying subsystem should be able to dry the body in 3,35 min.…”
Section: Figure 5: Schematic Representation Of the Conjugation Betweementioning
confidence: 99%
“…Comparison of alternatives can be made for retrofitting of installations [6][7][8][9] or at a design stage (case study herein presented).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies and reports on which option for hand drying is the most hygienic, economic, or efficient [9][10][11], however conflict of interests were identified in most publications. Another study revealed that there is no significant association between the drying method and the proliferation of bacteria [12].…”
Section: Introductionmentioning
confidence: 99%